Preparation and characterization of antiadhesion barrier film from hyaluronic acid-grafted electrospun poly(caprolactone) nanofibrous membranes for prevention of flexor tendon postoperative peritendinous adhesion - Chen SH (Dove Medical Press, 2014)
Shih-Hsien Chen,1 Chih-Hao Chen,1,2 KT Shalumon,1 Jyh-Ping Chen1,3 1Department of Chemical and Materials Engineering, 2Department of Plastic and Reconstructive Surgery, Chang Gung Memorial Hospital, College of Medicine, Chang Gung University, 3Research Center for Industry of Human Ecology, Chang Gung University of Science and Technology, Taoyuan, Taiwan, Republic of China Abstract: Peritendinous adhesion is one of the common complications encountered after tendon injury and subsequent surgery, and it can be minimized by introducing a physical barrier between the injured site and the surrounding tissue. An electrospun hyaluronic acid-grafted poly(caprolactone) (PCL-g-HA) nanofibrous membrane (NFM) is proposed as an alternative to current antiadhesion barrier films. HA is covalently grafted to surface-aminolyzed PCL nanofibers, using carbodiimide as the coupling agent. Pristine PCL and PCL-g-HA NFMs were characterized by scanning electron microscopy, thermogravimetric analysis, X-ray photoelectron spectroscopy, Fourier-transform infrared spectroscopy, and mechanical testing. In vitro cell culture with fibroblasts showed that PCL-g-HA NFMs reduced cellular adhesion on the membrane surface while maintaining cell proliferation. Animal experiments using a rabbit flexor digitorum profundus tendon model confirmed the efficacy of PCL-g-HA in reducing peritendinous adhesion, based on gross observation, histology, joint flexion-angle measurements, gliding tests, and biomechanical evaluation. Keywords: peritendinous adhesion, hyaluronic acid, polycaprolactone, antiadhesion, nanofibrous membranes, barrier film, surface grafting